PROTOTYPING MODEL IN INFORMATION SYSTEM DEVELOPMENT OF AL-RUHAMAA' BOGOR YATIM CENTER FOUNDATION - Wulandari, Dewi Ayu Nur; Bahar, Asyil Alfin Halani; Arfananda, Muhammad Ghifari; Apriyani, Helina (LPPM Universitas Nusa Mandiri, 2021)
The information system for providing donations at the Al-Ruhamaa' Bogor Yatim Center Foundation is still not computerized, through donors coming to the location directly or through bank services, then confirmed via social media such as WhatsApp, and receiving proof of donation in the form of a receipt. The management of the Al-Ruhamaa' Bogor Yatim Center Foundation stills using Microsoft Excel to prepare donation reports. Based on the existing problems, it is necessary to develop an information system for distributing donations that can facilitate the management and the donors of the Al-Ruhamaa' Bogor Yatim Center Foundation. The system will be developed using one of the techniques commonly used in software development is called the prototyping model. the prototyping model is a technique to collect certain information about the user's information needs quickly which focuses on aspects of the software to be presented that will be visible to the customer or user. After the system is implemented, it is found that by using this Information System, the donation transaction process becomes more efficient. Calculation of the number of donations collected can be done automatically and accurately. In terms of reporting, the system can be present donation reports automatically and is ready to print whenever needed. Data storage for documentation of activities carried out by the foundation also saves space because the information can be accessed anytime and anywhere.